Proceedings of the FAO Rice Conference 2004 : (Food and Agirculture Organization of the United Nations, 2005)
The International Year of Rice (IYR) promotes improved production and access to this vital food crop, which feeds more than half the world's population while providing income for millions of rice producers, processors and traders. To celebrate IYR, FAO convened and international rice conference, which was open to the participation of governments, research institutions, non-governmental organizations, and the private sector. The growth in rice consumption has starting to slow down; this publication aims to explain why and how, and draws together all the presentations pertaining to one of the general themes of the Conference: rice in the context of global markets.